A kind of CMP polishing liquid for rough polishing of aluminum nitride ceramics and preparation method thereof

By developing a CMP polishing liquid for aluminum nitride ceramics, the problems of difficult processing, high surface roughness and long polishing time of aluminum nitride ceramics are solved, and the surface roughness, shortening polishing time and reducing cost are achieved, while ensuring environmental protection and equipment versatility.

CN119752326APending Publication Date: 2025-04-04GANSU JINYANG HIGH-TECH MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967469.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Aluminum nitride ceramics are difficult to process, have high surface roughness and long polishing time.

Method used

A CMP polishing liquid for aluminum nitride ceramics is developed, and its components include abrasives, chelating agents, dispersants, thickening agents, moisturizers, surfactants and pH adjusters. Through specific ratios and preparation methods, a polishing liquid with a pH of 11.5-12.5 is prepared.

Benefits of technology

The surface roughness is less than 22nm, which reduces the time of finishing, reduces costs, and improves efficiency. The polishing liquid has strong versatility to the equipment, the raw materials used are easy to handle, and has no pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752326A_ABST
    Figure CN119752326A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of aluminum nitride ceramic rough polishing, specifically to a CMP polishing liquid for aluminum nitride ceramic rough polishing and a preparation method thereof, wherein the polishing liquid comprises: 8%-20% wt of abrasive, 0.5%-1.5% wt of chelating agent, 1%-3% wt of dispersant, 0.5%-1.5% wt of thickener, 5%-15% wt of moisturizing agent, 0.1%-1.0% wt of surfactant, pH regulator, and the balance is deionized water. The present invention develops a polishing liquid for aluminum nitride ceramics, wherein the pH of the polishing liquid is 11.5-12.5, the surface roughness is less than 22nm, the optimal surface roughness is less than 15nm, there is no damaged layer on the surface after polishing, the time of fine polishing is reduced, the cost is reduced, the efficiency is improved, the polishing liquid has strong versatility for equipment, the raw materials used are easy to handle, and there is no pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum nitride ceramic rough polishing, in particular to a CMP polishing liquid for aluminum nitride ceramic rough polishing and a preparation method thereof. Background Art

[0002] Aluminum nitride (AlN) is a new type of semiconductor material with the advantages of high thermal conductivity, large bandgap, stable chemical properties and non-toxicity. Compared with silicon, it can achieve a similar thermal expansion coefficient and excellent mechanical strength. As the most ideal substrate material for high-integration and high-power device packaging, it can meet the new demands of semiconductor devices and has good application prospects in aerospace, automobiles, chips and national defense industry.

[0003] At present, the main methods for flattening the surface of aluminum nitride ceramics are grinding and polishing. The abrasives used in the grinding process include diamond powder, silicon carbide, etc. The purpose of grinding is to remove the wire cutting marks. However, due to the high hardness of the abrasive particles used in grinding, the surface is severely damaged after grinding and cannot be put into use directly, so it needs to be polished for further processing; polishing is mainly divided into two processes: rough polishing and fine polishing. Rough polishing is to quickly remove the damaged layer and further reduce the surface roughness, laying the foundation for fine polishing. Rough polishing requires a surface roughness of 50nm and no damaged layer, while fine polishing generally uses silica sol and requires its surface roughness to be less than 8nm. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a CMP polishing liquid for aluminum nitride ceramics and a preparation method thereof, so as to solve the problems of the prior art that aluminum nitride ceramics are difficult to process, have high surface roughness, and take a long time to polish.

[0005] In order to achieve the above object, the technical solution provided by the present invention is as follows:

[0006] A CMP polishing liquid for aluminum nitride ceramics, characterized in that the polishing liquid comprises the following components: 8%-20% by weight of abrasive, 0.5%-1.5% by weight of chelating agent, 1%-3% by weight of dispersant, 0.5%-1.5% by weight of thickener, 5%-15% by weight of humectant, 0.1%-1.0% by weight of surfactant, pH regulator, and the balance is deionized water.

[0007] Preferably, the abrasive is one or more of 0.2 μm α-alumina, 0.6 μm α-alumina, and 1.0 μm α-alumina.

[0008] Preferably, the chelating agent is one or more of disodium ethylenediaminetetraacetate, hydroxyethylidene diphosphonic acid, sodium gluconate, and sodium citrate.

[0009] Preferably, the dispersant is one or more of sodium methylene bis(methyl naphthalene sulfonate), sodium polyacrylate, and sodium hexametaphosphate.

[0010] Preferably, the thickener is one or more of sodium carboxymethyl cellulose, lithium magnesium silicate, sodium hydroxyethyl cellulose, and polyvinyl pyrrolidone.

[0011] Preferably, the surfactant is one or more of fatty alcohol polyoxyethylene ether, sodium lauryl sulfate, sodium allyl sulfonate, and Tween 60.

[0012] Preferably, the pH regulator is one or more of potassium hydroxide, cesium hydroxide, triethanolamine, and tetrahydroxyethylethylenediamine.

[0013] Preferably, the humectant is one or more of polyglycerol-10, glycerol, and sorbitol.

[0014] A method for preparing a CMP polishing liquid for aluminum nitride ceramics, characterized in that it comprises the following steps:

[0015] Step 1, weigh 1%-3% wt of the dispersant, add it to 84.9%-58% wt of deionized water and stir until completely dissolved;

[0016] Step 2, weigh 0.5%-1.5% Wt of thickener, add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0017] Step 3, weighing 0.5%-1.5% wt of a chelating agent and 0.1%-1% wt of a surfactant, adding them to the suspension in step 2, and stirring for 20 minutes until they are completely dissolved;

[0018] Step 4, weigh 5%-15% wt of moisturizer and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0019] Step 5, weigh 8%-20% wt of abrasive and add a small amount of slurry to the solution in step 4 in a stirring state in small amounts, mix them thoroughly and evenly, and adjust the pH of the polishing liquid with a pH regulator so that the pH is stabilized at 11.5-12.5;

[0020] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain the aluminum nitride ceramic coarse polishing liquid.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention develops a polishing liquid for aluminum nitride ceramics. The pH value of the polishing liquid is 11.5-12.5, the surface roughness is less than 22nm, the optimal surface roughness is less than 15nm, there is no damaged layer on the surface after polishing, the time for fine polishing is reduced, the cost is reduced, the efficiency is improved, the polishing liquid has strong versatility for equipment, the raw materials used are easy to handle, and there is no pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a surface roughness picture of sample 1# in Example 1 of the present invention;

[0024] Figure 2 This is a surface roughness image of sample 2# in Example 1 of the present invention;

[0025] Figure 3 This is a surface roughness image of sample 3# in Example 1 of the present invention;

[0026] Figure 4 This is a surface roughness image of sample 4# in Example 2 of the present invention;

[0027] Figure 5 This is a surface roughness picture of sample 5# in Example 2 of the present invention;

[0028] Figure 6 This is a surface roughness picture of sample 6# in Example 2 of the present invention;

[0029] Figure 7 This is a surface roughness picture of sample 7# in Example 3 of the present invention;

[0030] Figure 8 This is a surface roughness picture of sample 8# in Example 4 of the present invention;

[0031] Fig. 9 This is a surface roughness picture of sample 9# in Example 5 of the present invention;

[0032] Fig.10 This is a surface roughness picture of sample 10# in Example 6 of the present invention;

[0033] Fig.11 This is a surface roughness image of sample 11# in Example 7 of the present invention;

[0034] Fig.12 This is a surface roughness picture of sample 12# in Example 8 of the present invention;

[0035] Fig.13 This is a surface roughness image of sample 13# in Example 9 of the present invention;

[0036] Fig.14 This is a surface roughness image of sample 14# in Example 9 of the present invention;

[0037] Fig.15 This is a surface roughness picture of sample 15# in Example 9 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The prepared aluminum nitride ceramic rough polishing liquid, all embodiments were compared and tested according to the following conditions and polishing parameters:

[0040]

[0041] Example 1

[0042] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0043] Step 1, weigh 3 parts of 1% wt sodium methylene bis(methyl naphthalene sulfonate), add them into 76.9% wt, 76.4% wt and 75.9% wt deionized water and stir until completely dissolved;

[0044] Step 2, weigh 0.5% wt of sodium carboxymethyl cellulose, add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0045] Step 3, weigh 0.5% wt sodium citrate as 1#, 1.0% wt sodium citrate as 2#, 1.5% wt sodium citrate as 3#, and 3 parts of 0.1% wt fatty alcohol polyoxyethylene ether, add them to the suspension of step 2 and stir until completely dissolved;

[0046] Step 4, weigh 10% Wt of polyglycerol-10 and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0047] Step 5, weigh 16% wt 0.2 μm α-alumina slurry and add it to the stirring solution of step 4 in small portions, and adjust the pH to 11.5-12.5 with triethanolamine;

[0048] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain samples 1#, 2#, and 3#.

[0049] like Figure 1-3As shown, the results show that the initial value of the roughness Sa is 357.931nm, the surface roughness Sa of sample 1# is 17.703nm, and the removal amount is 16um / h; the surface roughness Sa of sample 2# is 17.784nm, and the removal amount is 18.5μm / h; the surface roughness Sa of sample 3# is 17.600nm, and the removal amount is 16.5μm / h.

[0050] Example 2

[0051] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0052] Step 1, weigh 3% wt of sodium polyacrylate and add it into 71.5% wt, 65.5% wt and 59.5% wt of deionized water respectively and stir until completely dissolved;

[0053] Step 2, weigh 1% Wt of polyvinyl pyrrolidone and add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0054] Step 2, weigh 1% wt of disodium ethylenediaminetetraacetate and 0.5% wt of sodium allyl sulfonate, add them to the suspension in step 2 and stir until completely dissolved;

[0055] Step 3, weigh 15% Wt of polyglycerol-10 and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0056] Step 4, weigh 8% wt, 14% wt, 20% wt 1.0 μm α-alumina as 4#, 5#, 6#, add a small amount to the stirring solution of step 4 in batches, and adjust the pH to 11.5-12.5 with tetrahydroxyethylethylenediamine;

[0057] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain samples 4#, 5#, and 6#.

[0058] like Figure 4-6 As shown, the results show that the initial value of the roughness Sa is 367.782nm, the surface roughness Sa of sample 4# is 17.364nm, and the removal amount is 17um; the surface roughness Sa of sample 5# is 13.032nm, and the removal amount is 18μm; the surface roughness Sa of sample 6# is 17.441nm, and the removal amount is 19μm.

[0059] Example 3

[0060] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0061] Step 1, weigh 3% wt of sodium polyacrylate, add it into 59.7% wt of deionized water and stir until it is completely dissolved;

[0062] Step 2: 1% Wt of polyvinyl pyrrolidone is added to the solution of step 1 and stirred for 60 minutes to fully dissolve it and form a suspension;

[0063] Step 3, weigh 0.8% wt of sodium gluconate and 0.5% wt of sodium allyl sulfonate, add them to the suspension in step 2 and stir until completely dissolved;

[0064] Step 4, weigh 15% wt of sorbitol and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0065] Step 5, weigh 20% wt 0.2 μm α-alumina and add it in small amounts to the stirring solution of step 4, and adjust the pH to 11.5-12.5 with tetrahydroxyethylethylenediamine;

[0066] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain sample #7.

[0067] like Figure 7 As shown, the results show that the initial value of the roughness Sa is 351.261nm, the surface roughness Sa of sample 7# is 21.846nm, and the removal amount is 17um.

[0068] Example 4

[0069] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0070] Step 1, weigh 1.5% wt of sodium hexametaphosphate, add it into 73.2% wt of deionized water and stir until it is completely dissolved;

[0071] Step 2, weigh 0.8% wt of sodium hydroxyethyl cellulose and add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0072] Step 3, weigh 1.5% wt of hydroxyethyl diphosphonic acid and 1% wt of sodium dodecyl sulfate, add them to the suspension in step 2 and stir until completely dissolved;

[0073] Step 4, weigh 10% wt of glycerol and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0074] Step 5, weigh 12% wt 0.2 μm α-alumina and add it in small amounts to the stirring solution of step 4, and adjust the pH to 11.5-12.5 with potassium hydroxide;

[0075] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain sample #8.

[0076] like Figure 8As shown, the results show that the surface roughness Sa of sample 7# is 21.621nm and the removal amount is 20um.

[0077] Example 5

[0078] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0079] Step 1, weigh 2% wt of sodium polyacrylate, add it into 71.8% wt of deionized water and stir until it is completely dissolved;

[0080] Step 2, weigh 1.5% wt of lithium magnesium silicate and add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0081] Step 3, weigh 1% wt of disodium ethylenediaminetetraacetate and 0.7% wt of Tween 60, add the suspension in step 2 and stir until completely dissolved;

[0082] Step 4, weigh 8% wt of sodium lactate and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0083] Step 5, weigh 15% wt 0.6 μm α-alumina and add it in small amounts to the stirring solution of step 4, and adjust the pH to 11.5-12.5 with cesium hydroxide;

[0084] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain a 9# sample.

[0085] like Fig. 9 As shown, the results show that the surface roughness Sa of sample 9# is 19.798nm and the removal amount is 17um.

[0086] Example 6

[0087] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0088] Step 1, weigh 2% wt of sodium polyacrylate, add it into 76.5% wt of deionized water and stir until it is completely dissolved;

[0089] Step 2, weigh 0.5% wt of sodium hydroxyethyl cellulose and add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0090] Step 3, weigh 1% wt of disodium ethylenediaminetetraacetate and 1% wt of sodium dodecyl sulfate, add them to the suspension in step 2 and stir until completely dissolved;

[0091] Step 4, weigh 13% wt of glycerol and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0092] Step 5, weigh 16% wt 1.0 μm α-alumina and add it to the stirring solution of step 4 in small portions, and adjust the pH to 11.5-12.5 with cesium hydroxide;

[0093] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain a 10# sample.

[0094] like Fig.10 As shown, the results show that the surface roughness Sa of sample 10# is 16.161nm and the removal amount is 18um.

[0095] Example 7

[0096] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0097] Step 1, weigh 2% wt of sodium polyacrylate, add it into 76.4% wt of deionized water and stir until it is completely dissolved;

[0098] Step 2, weigh 0.8% wt of sodium hydroxyethyl cellulose and add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0099] Step 3, weigh 0.8% wt of sodium citrate and 1% wt of sodium dodecyl sulfate, add them to the suspension in step 2 and stir until completely dissolved;

[0100] Step 4, weigh 13% wt of glycerol and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0101] Step 5, weigh 16% wt 1.0 μm α-alumina and add it to the stirring solution of step 4 in small portions, and adjust the pH to 11.5-12.5 with potassium hydroxide;

[0102] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain sample #11.

[0103] like Fig.11 As shown, the results show that the surface roughness Sa of sample 11# is 19.167nm and the removal amount is 18um.

[0104] Example 8

[0105] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0106] Step 1, weigh 2% wt of sodium polyacrylate, add it into 66% wt of deionized water and stir until it is completely dissolved;

[0107] Step 2, weigh 1.2% wt of sodium hydroxyethyl cellulose and add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0108] Step 3, weigh 0.8% wt of sodium citrate and 1% wt of sodium dodecyl sulfate, add them to the suspension in step 2 and stir until completely dissolved;

[0109] Step 4, weigh 13% wt of glycerol and add it to the solution in step 3, and set the stirring time to 30 minutes;

[0110] Step 5, weigh 16% wt 1.0 μm α-alumina and add it to the stirring solution of step 4 in small portions, and adjust the pH to 11.5-12.5 with potassium hydroxide;

[0111] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain a 12# sample.

[0112] like Fig.12 As shown, the results show that the surface roughness Sa of sample 12# is 17.210nm and the removal amount is 16um.

[0113] Example 9

[0114] The aluminum nitride ceramic polishing liquid prepared in this embodiment is prepared by the following method:

[0115] Step 1, weigh 3 parts of 2% wt sodium polyacrylate, add 73.9% wt, 69.9% wt, and 65.9% wt deionized water and stir until completely dissolved;

[0116] Step 2, weigh 0.8% wt of lithium magnesium silicate and add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension;

[0117] Step 3, weigh 1% wt of disodium ethylenediaminetetraacetate and 0.3% wt of Tween 60, add the suspension in step 2 and stir until completely dissolved;

[0118] Step 4, weigh 6%Wt, 10%Wt, and 14%Wt of sorbitol as samples 13#, 14#, and 15#, and add them to the solution in step 3, and set the stirring time to 30 minutes;

[0119] Step 5, weigh 16% wt 1.0 μm α-alumina and add it to the stirring solution of step 4 in small portions, and adjust the pH to 11.5-12.5 with potassium hydroxide;

[0120] Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain samples 13#, 14#, and 15#.

[0121] like Figure 13-15The results show that the surface roughness Sa of sample 13# is 12.918nm, the removal amount is 23um, the surface roughness Sa of sample 14# is 13.311nm, the removal amount is 20um, and the surface roughness Sa of sample 15# is 13.032nm, and the removal amount is 21um.

[0122] The comparative test data are as follows:

[0123]

[0124]

[0125] Comparative Examples and Test Result Analysis: In conjunction with the three samples of Example 1, it can be clearly seen that the chelating agent content gradually increases, the polishing rate shows a trend of first increasing and then decreasing, and the surface roughness Sa value does not change much. The chelating agent 0.5%-1.5% can achieve the surface roughness value and polishing rate, and the optimal chelating agent content is 0.5%-1.0%; In conjunction with the three samples of Example 2, the abrasive increases with the increase in the amount of addition, the polishing rate gradually increases, and the surface roughness has a trend of first decreasing and then increasing. The abrasive content between 8%-20% can meet the requirements, and the abrasive between 8%-14%, the surface roughness decreases most significantly; the central particle size of the abrasive is 0.2μm, 0.6μm, 1.0μm, and there is no difference in the influence on the surface roughness and polishing rate at different concentrations. The requirements are different; the thickener can meet the requirements at 0.5%-1.5%, and the surface roughness and rate are reduced at 0.8%-1.2%. Considering the two factors of polishing rate and surface roughness, the optimal content of the thickener is 0.5%-0.8%; Combining the three samples of Example 9, it can be clearly seen that the polishing rate gradually decreases with the gradual increase of the moisturizing agent content, and the surface roughness Sa value does not change substantially. The polishing rate of 6%-10% is faster than that of 10%-14%, and the optimal content of the moisturizing agent is 6%-10%; All types of pH regulators between 11.5-12.5 can meet the requirements; Comprehensive comparison of 15 samples, sample 9# and sample 11# have the smoothest surfaces, and sample 11 is the best overall, with a surface roughness Sa of 19.167nm and a removal amount of 48μm.

[0126] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A CMP polishing liquid for aluminum nitride ceramics, characterized in that: The polishing liquid comprises the following components: 8%-20% by weight of abrasive, 0.5%-1.5% by weight of chelating agent, 1%-3% by weight of dispersant, 0.5%-1.5% by weight of thickener, 5%-15% by weight of moisturizing agent, 0.1%-1.0% by weight of surfactant, pH regulator, and the balance is deionized water.

2. The CMP polishing liquid for rough polishing of aluminum nitride ceramics according to claim 1, characterized in that: The abrasive is one or more of 0.2 μm α-alumina, 0.6 μm α-alumina, and 1.0 μm α-alumina.

3. The CMP polishing liquid for rough polishing of aluminum nitride ceramics according to claim 1, characterized in that: The chelating agent is one or more of disodium ethylenediaminetetraacetate, hydroxyethylidene diphosphonic acid, sodium gluconate and sodium citrate.

4. The CMP polishing liquid for rough polishing of aluminum nitride ceramics according to claim 1, characterized in that: The dispersant is one or more of sodium methylene bis(methyl naphthalene sulfonate), sodium polyacrylate, and sodium hexametaphosphate.

5. The CMP polishing liquid for rough polishing of aluminum nitride ceramics according to claim 1, characterized in that: The thickener is one or more of sodium carboxymethyl cellulose, lithium magnesium silicate, sodium hydroxyethyl cellulose and polyvinyl pyrrolidone.

6. The CMP polishing liquid for rough polishing of aluminum nitride ceramics according to claim 1, characterized in that: The surfactant is one or more of fatty alcohol polyoxyethylene ether, sodium lauryl sulfate, sodium allyl sulfonate, and Tween 60.

7. The CMP polishing liquid for rough polishing of aluminum nitride ceramics according to claim 1, characterized in that: The pH regulator is one or more of potassium hydroxide, cesium hydroxide, triethanolamine, and tetrahydroxyethylethylenediamine.

8. The CMP polishing liquid for rough polishing of aluminum nitride ceramics according to claim 1, characterized in that: The moisturizing agent is one or more of polyglycerol-10, glycerin and sorbitol.

9. A method for preparing a CMP polishing liquid for aluminum nitride ceramics, characterized in that: The following steps are involved: Step 1, weigh 1%-3% wt of the dispersant, add it to 84.9%-58% wt of deionized water and stir until completely dissolved; Step 2, weigh 0.5%-1.5% Wt of thickener, add it to the solution in step 1 and stir for 60 minutes to fully dissolve it and form a suspension; Step 3, weighing 0.5%-1.5% wt of a chelating agent and 0.1%-1% wt of a surfactant, adding them to the suspension in step 2, and stirring for 20 minutes until they are completely dissolved; Step 4, weigh 5%-15% wt of moisturizer and add it to the solution in step 3, and set the stirring time to 30 minutes; Step 5, weigh 8%-20% wt of abrasive and add a small amount of slurry to the solution in step 4 in a stirring state in small amounts, mix them thoroughly and evenly, and adjust the pH of the polishing liquid with a pH regulator so that the pH is stabilized at 11.5-12.5; Step 6: Filter the prepared slurry through a 400-mesh stainless steel sieve to obtain the aluminum nitride ceramic coarse polishing liquid.